Forest-based bioeconomy in sub-Saharan Africa: Looking at benefits and burdens from a social sustainability standpoint - Rosa, S.F.P.; Martius, C. (Center for International Forestry Research, 2021)
Populations in sub-Saharan Africa (SSA) living on the fringes of forests indubitably rely on them for income and subsistence. But unsustainable practices can lead to resource degradation and depletion, threatening the very basis of their livelihoods. A forest-based ‘circular’ bioeconomy approach could stabilize sustainable natural resource use, yet bioeconomy strategies so far have focused mostly on technology and economics, rather than on matters of social sustainability. This study reviews literature published between 2000 and 2020, with the aim of identifying whether socio-economic impacts were taken into account in the forest sectors and bioeconomy elements covered in this SSA-focused literature. Many studies investigate forest-related value chain development across a forest sector that remains mostly traditional and largely informal. Non-timber forest products (NTFPs) play a significant role and could represent an entry point for bioeconomy development. Energy security could also benefit from taking a bioeconomy perspective. Forest activities resulted in positive social outcomes in just a third of the studied cases. Challenges to bioeconomy development include uncoordinated and often bureaucratic forest policies and regulations, as well as overlaps and clashes between formal and informal economic activities and land tenure regimes. Lack of knowledge and skills – around entrepreneurship, investment and finance – further hampers development. In conclusion, while forest-based bioeconomy could enrich the forest sector and contribute to poverty reduction and natural resource conservation, strategies must adopt a strong social sustainability approach, or this transition risks reproducing patterns of land grabbing, elite capture, spatial injustice and the displacement and disempowerment of rural populations.